2015
DOI: 10.1111/lnc3.12163
|View full text |Cite
|
Sign up to set email alerts
|

Second Dialect Acquisition: A Sociophonetic Perspective

Abstract: Many people change aspects of their accent after moving to a new region. What kinds of changes are made, and why does it matter? Studies of second dialect acquisition (SDA) indicate that geographically mobile speakers change specific dialect features in ways that ref lect the complex interaction of linguistic, social, and developmental factors in language use. This article reviews these findings from a sociophonetic perspective, paying particular attention to their theoretical implications, the methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 66 publications
1
30
0
1
Order By: Relevance
“…The fact that there were such wide‐ranging rates of r‐lessness across this group thus demonstrates that time of exposure to a new dialect alone is also not necessarily the key to understanding language patterns. One point worth addressing, however, is that being displaced for seven years starting at age 78 (the age of the oldest participant in the sample when Katrina hit) is quite a different affair from relocating at age 11 (the age of the youngest participant when Katrina hit), since age‐of‐arrival has been found to be a significant contributor to second dialect acquisition (Fix ; Nycz ). And indeed, it was noted above that participants under 30 years of age were more likely to be categorically r‐ful than participants over 30, which suggests there may be linguistic effects of Hurricane Katrina that simply have not become clear yet in the time that has passed since the storm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that there were such wide‐ranging rates of r‐lessness across this group thus demonstrates that time of exposure to a new dialect alone is also not necessarily the key to understanding language patterns. One point worth addressing, however, is that being displaced for seven years starting at age 78 (the age of the oldest participant in the sample when Katrina hit) is quite a different affair from relocating at age 11 (the age of the youngest participant when Katrina hit), since age‐of‐arrival has been found to be a significant contributor to second dialect acquisition (Fix ; Nycz ). And indeed, it was noted above that participants under 30 years of age were more likely to be categorically r‐ful than participants over 30, which suggests there may be linguistic effects of Hurricane Katrina that simply have not become clear yet in the time that has passed since the storm.…”
Section: Discussionmentioning
confidence: 99%
“…The marked quality of r‐lessness within GNO is significant, since research on migration and second dialect acquisition has demonstrated that stigmatized and ideologically marked linguistic features are often those most likely to be dropped when speakers leave their home dialect area – unless there are attitudinal or identity‐driven reasons for retaining them (Auer, Barden and Grosskopf , ; Meyerhoff and Walker ; Hazen and Hamilton ; Nycz ). Salience of linguistic features has also been shown to be a significant predictor of linguistic choices in contexts of movement or displacement (Stanford and Pan ; Cotter and Horesh ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions of ability and control of styles have been noted in the literature, in relation to creoles (Le Page & Tabouret-Keller 1985), second dialect acquisition and shift (e.g. Auer, Hinskens, & Kerswill 2005;Tagliamonte & Molfenter 2007;Siegel 2010;Smith & Durham 2012;Fix 2013;Nycz 2015), crossing, passing, and performative range (e.g. Cutler 1999;Piller 2002;Sweetland 2002;Coupland 2007:103;Guy & Cutler 2011;Zimman 2016), routine variation (Schilling-Estes 2004; Kendall 2013), perception (e.g.…”
Section: S T Y L E a N D A T T E N T I O Nmentioning
confidence: 99%
“…However, speakers may also be exposed to new dialects of an L2 (Drummond, 2013) or to dialects associated with different ethnic groups or social classes (Fix 2014;Hazen, 2001;Siegel 2010). Acquisition can be evidenced by changes in speech perception and/or speech production, though changes in production may be more salient to both speakers and researchers (for more discussion of perception in dialect acquisition and what it means to "have" an accent, see Nycz, 2015;Walker, 2018). While the phrase "second dialect acquisition" may imply that a whole new linguistic system is learned (or is the target of learning), the sociolinguistic research in this field indicates that this rarely if ever happens.…”
Section: Second Dialect Acquisitionmentioning
confidence: 99%